Legal Protection of Consumers in Transactions E-Commerce in Indonesia - Irma Roudlotul Jannah; Helna Tri Syanturi; Arif Zunaidi (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2025)
The development of information technology has driven the rapid growth of e-commerce in Indonesia. Online transactions offer convenience for consumers, but also present various potential risks such as fraud, unsuitable goods, and data privacy violations. This research aims to analyze the legal protection provided to consumers in e-commerce transactions, as well as the effectiveness of existing regulations in guaranteeing consumer rights. The method used is a normative juridical approach by examining laws and regulations such as Law Number 8 of 1999 concerning Consumer Protection, ITE Law, and Government Regulation No. 80 of 2019 concerning Trading Through Electronic Systems. The results showed that although regulations are available, the implementation of legal protection for consumers still faces challenges, especially in the aspects of law enforcement and consumer education. Therefore, collaborative efforts between the government, business actors, and the community are needed to create a safe and fair e-commerce ecosystem for consumers.